REWRITING GLOBAL HEALTH MAPS: INDONESIA’S STRATEGIC REALIGNMENT AND WHO REGIONALISM'S FUTURE - Ridlo, Ilham Akhsanu (Universitas Airlangga, 2025)
This commentary discusses Indonesia's strategic decision to move from the WHO Southeast Asia region (SEARO) to the Western Pacific region (WPRO), which was formally approved at the 78th World Health Assembly in May 2025. This move shows that Indonesia wants to be more active in determining the direction of its global health cooperation, while also revealing power imbalances and limitations in the WHO regional system. The article also compares Indonesia's experience with other countries, such as Mongolia and Israel, that have made similar moves. It concludes that the WHO's regional system needs to be adjusted to be more equitable and flexible, and give all member states an equal voice. Keywords: Global health, Indonesia, multilateralism, regionalism, power asymmetry.